Currículo, educação à distância e cultura do estudo autônomo em curso de Pedagogia: limites e possibilidades - Anaya, Viviani (2013)
This research discusses distance education and the culture of self-study, with a view to a more active and effective participation of students in the process of knowledge construction. Therefore, the concept of autonomy becomes crucial role to play. In this research, the culture of self-study emerges as a central element and is discussed from the standpoint of contemporary, pointing to overthrow the boundaries of time and space, influencing greatly in the concept of autonomy. The notions of time, space, criticality, reflexivity, autonomy, empowerment, interpersonal relationships, meaningful learning, are striking features when the focus is on distance learning courses, as the notion of linear time and space and Cartesian posed by classroom education in distance learning courses, are gradually replaced by the space occupied virtually therefore more flexible as well as study time determined by academic independently defined. These concepts emerge exacerbated because the configuration of a course offered in distance mode presupposes knowledge and internalization of these elements by students, becoming a "sine qua non" for the continuation of studies. However, other factors influence the formation this autonomous culture. These secondary elements, namely, the organizational structure of the curriculum, the didactic aspects, methodological and evaluative, as well as materials available in virtual learning environments, permeate this search and constitute themselves into categories, providing elements for the analysis of data collected research, allowing the definition of the question that guides research: What are the limits and possibilities that pervades higher education in distance mode, considering the culture of self-study, teaching practice undertaken by teachers / tutors and curriculum of a course in pedagogy? Defined the issue, determine the locus and the research subjects. This study aims to contribute to general discussions about the limits and possibilities of higher education in the distance mode, considering the culture of self-study, teaching practice undertaken by teachers / tutors and curriculum of the Faculty of Education, object of this analysis. Specifically, this study attempts to identify if the student opts for distance education has the culture of self-study, identify the digital culture is present in the daily student who opts for distance mode; relate teaching practices, culture and self-study distance learning, recognize the importance of concepts such as autonomy, emancipation, reflexivity, collaborative work, interpersonal relationships, meaningful learning, while categories to be included in structured courses in distance mode. In this research, a qualitative approach guides both the collection of data regarding the analysis of the data collected thus abstracts itself as hypothesis, that the student who opts for training in distance mode, does not possess the culture of self-study. With this focus, this research aims to contribute to a better understanding of the condition students in distance education. This condition is established from the contemporary discussion about the culture of self-study, changing the architecture curriculum, education and geography teachers s pedagogic practice